INTELLIGENCE TEST SIMULATION APPLICATION ON MOBILE WEB-BASED CHILDREN ON ANDROID PLATFORM - Puspita, Dian; Alexsander, Gilbert; Mukodimah, Siti (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2022)
One real system that requires a mobile web-based simulation application is the implementation of an intelligence test. This is because this intelligence test requires high mobility and accurate information distribution and fast service. So far, IQ testing has always been carried out by other institutions at a high cost and the IQ test results are processed very slowly to determine the IQ test results. Making a mobile web-based test simulation application system implemented on Android and oriented with a simple and lightweight concept will certainly make users more comfortable and easier to use. The benefit of this application is that users can carry out intelligence test simulations through different device platforms and operating systems. Users can immediately see the test results at that time too. The implementation of the IQ test can be done at any time from various places as long as it has an android application and is connected to an internet network. This application was developed using the System Development Life Cycle (SDLC) method which has development stages covering system analysis, system design, system implementation, and system testing. System analysis is carried out to determine data, information, hardware, and software needs. System design includes model design, database design, and interface design to facilitate implementation. The system is implemented based on the mobile web with HTML, JavaScript, Atom, and Ionic Framework programming languages. The web server uses NodeJs. System testing is done in two ways, namely black box testing and Alpha testing. Based on the results of black box testing and Alpha testing, the developed application meets predetermined specifications, can run properly, is very easy to use, has an attractive appearance, is complete, and has very fast access.